2021
DOI: 10.3390/pr9050849
|View full text |Cite
|
Sign up to set email alerts
|

Heat Transfer and Hydrodynamics in Stirred Tanks with Liquid-Solid Flow Studied by CFD–DEM Method

Abstract: The heat transfer and hydrodynamics of particle flows in stirred tanks are investigated numerically in this paper by using a coupled CFD–DEM method combined with a standard k-e turbulence model. Particle–fluid and particle–particle interactions, and heat transfer processes are considered in this model. The numerical method is validated by comparing the calculated results of our model to experimental results of the thermal convection of gas-particle flows in a fluidized bed published in the literature. This cou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(5 citation statements)
references
References 44 publications
0
5
0
Order By: Relevance
“…This work considers the heat transfer between 'particle-particle' and 'particle-fluid'. The energy control equation for a single particle is as follows [17,[23][24][25][26][27]:…”
Section: Governing Equations For Gas Phasementioning
confidence: 99%
See 2 more Smart Citations
“…This work considers the heat transfer between 'particle-particle' and 'particle-fluid'. The energy control equation for a single particle is as follows [17,[23][24][25][26][27]:…”
Section: Governing Equations For Gas Phasementioning
confidence: 99%
“…The standard k-ε turbulence model in ANSYS, the SST k-omega equation, is used as the turbulence model. The Ranz and Marshall heat transfer model and multicomponent model [15][16][17][18][19] are used because heat and mass transfer are considered in the work. In the component set, two compositions are identified: the evaporable component of water and a non-evaporable component of tiger nuts; the composition ratio is 45% and 55%, respectively.…”
Section: Simulation Conditionsmentioning
confidence: 99%
See 1 more Smart Citation
“…The CFD-DEM model is extensively used for simulating solid–liquid suspensions. Sun et al developed a method coupling the volume of fluid (VOF) method with the discrete element model (DEM) based on CFD-DEM for simulating free-surface solid–liquid flow with complex wall boundaries . Our team previously developed the DEM–VOF method for turbulent free-surface solid–liquid flows in complex geometries and applied it to the study of stirred tanks. …”
Section: Introductionmentioning
confidence: 99%
“…Li et al 8 carried out a simulation of an unbaffled stirred tank reactor driven by a magnetic stirring rod by Euler-Euler model coupled with the volume of fluid (VOF) method, and results showed that LES model and RNG k-epsilon model can predict the better tangential velocity and axial velocity. Luo et al 9 investigated the effects of geometrical and physical factors on light particles dispersion in stirred tank by agitation characteristic curve, and found that the agitation characteristic curves reflect the tendency of power consumption and particles distribution well in stirred tank. In addition, there are many researches 10 , 11 about simulation theory and methods of multiphase flow and corresponding case analysis.…”
Section: Introductionmentioning
confidence: 99%